Role of miRNA-671-5p in Mediating Wnt/β-Catenin-Triggered Podocyte Injury - Wang, Chunhong; Liu, Jiafeng; Zhang, Xiaoyao; Chen, Qiyan; Bai, Xiaoyan; Hong, Xue; Zhou, Lili; Liu, Youhua (Frontiers in Pharmacology, 2022)
Podocyte injury and proteinuria are the most common features of glomerular disease, which is the leading cause of end-stage renal failure. Hyperactivated Wnt/β-catenin signaling is closely associated with podocyte injury, but the underlying mechanisms are incompletely understood. Here we show that miRNA-671-5p plays a crucial role in mediating β-catenin-triggered podocyte injury by targeting Wilms tumor 1 (WT1). Microarray-based expression profiling revealed that miRNA-671-5p was the most upregulated miRNA in podocytes after β-catenin activation. MiRNA-671-5p was colocalized with β-catenin in the glomeruli of proteinuric CKD in vivo. Bioinformatics analyses and luciferase reporter assays confirmed that miRNA-671-5p targeted WT1 mRNA. Overexpression of miR-671-5p mimics inhibited WT1 and impaired podocyte integrity, whereas miR-671-5p antagomir preserved the expression of WT1 and other podocyte-specific proteins under basal conditions or after β-catenin activation. In mouse remnant kidney model, overexpression of miR-671-5p aggravated podocyte injury, worsened kidney dysfunction and exacerbated renal fibrosis after 5/6 nephrectomy. In contrast, miR-671-5p antagomir alleviated podocyte injury and attenuated proteinuria and renal fibrotic lesions after glomerular injury in vivo. These studies underscore a pivotal role of miRNA-671-5p in mediating WT1 depletion and podocyte injury induced by β-catenin. Targeting miR-671-5p may serve as a new approach to prevent podocyte injury and proteinuria in proteinuric CKD.